P-013 Technical aspects and clinical outcome of endovascular thrombectomy in octogenarians and nonagenarians: single center experience. (22nd July 2019) - Majidi, S; Lee, J; Al Balushi, A; Fifi, J; Singh, I
Abstract : Introduction/Purpose: Safety and efficacy of thrombectomy in patients ≥ 80 years old is not fully understood as this age group is generally underrepresented in major clinical trials. We aimed to review the procedural aspects and clinical outcome of thrombectomy in these patients. Materials and methods: We retrospectively identified all patients ≥ 80 years old who underwent thrombectomy for acute ischemic stroke with emergent large vessel occlusion (ELVO) in the anterior circulation from January 2014 to December 2018. Demographics, comorbidities, procedural variables, and clinical outcome measures were extracted. Thrombolysis in Cerebral Infarction (TICI) 2B or higher was considered successful reperfusion. Favorable clinical outcome was defined as a 90-day modified Rankin Scale (mRS) score<3. Results: A total of 113 patients were identified. The median age for the cohort was 85 years (range: 80–103). Seventy-three percent of the patients were women. Forty percent of the patients were white and 59% had Hispanic ethnicity. A total of 87 patients (77%) had internal carotid artery terminus or proximal M1 segment occlusion. Median admission NIHSS score was 18 (IQR: 14–25). Only 27% of the patients had received intravenous rt-PA. Thirty-two percent of the patients were treated between 6 hours to 24 hours from their time of symptom onset. Successful recanalization was achieved in 101 patients (89%) with a mean (±SD) groin puncture to recanalization time of 63±43 minutes. Monitored anesthesia care (MAC) was used in 78% of the patients. Groin puncture to recanalization time was 30 minutes shorter in patients under MAC (54±36 vs 85±50; p=0.0006); however, no statistically significant difference in the rate of 90-day favorable outcome was observed between the two groups (23% vs 20%, p=0.77). The rate of favorable 90-day outcome was 22% and 28 patients (39%) had 90-day mortality. Conclusions: Thrombectomy in octogenarians and nonagenarians is technically feasible and associated with high rate of recanalization. Although the 90-day mortality was elevated in our cohort, the natural history of completed stroke in this population without reperfusion is also high. Despite this finding, nearly one out of four patients in this study had a favorable clinical outcome. Disclosures: S. Majidi: None. J. Lee: None. A. Al Balushi: None. J. Fifi: None. I. Singh: None.